COVID-19 epidemiology in Canada from January to December 2020: the pre-vaccine era - David Waldner; Robyn Harrison; Jennie Johnstone; Lynora Saxinger; Duncan Webster; Wendy Sligl (Canadian Science Publishing, 2021)
This paper summarizes COVID-19 disease epidemiology in Canada in the pre-vaccine era-from January through to December 2020. Canadian case numbers, risk factors, disease presentations (including severe and critical disease), and outcomes are described. Differences between provinces and territories in geography, population size and density, health demographics, and pandemic impact are highlighted. Key concepts in public health response and mitigation are reviewed, including masking, physical distancing, hand washing, and the promotion of outdoor interactions. Adequate investment in public health infrastructure is stressed, and regional differences in screening and testing strategies are highlighted. The spread of COVID-19 in Canadian workplaces, long-term care homes, and schools is described and lessons learned emphasized. The impact of COVID-19 on vulnerable populations in Canada-including Indigenous Peoples, ethnic minorities and newcomers, people who use drugs, people who are homeless, people who are incarcerated, and people with disabilities-is described. Sex and gender disparities are also highlighted. Author recommendations include strategies to reduce transmission (such as test-trace-isolate), the establishment of nationally standardized definitions and public reporting, the protection of high risk and vulnerable populations, and the development of a national strategy on vaccine allocation.